Narrative Review of Neurologic Complications in Adults on ECMO: Prevalence, Risks, Outcomes, and Prevention Strategies - Zhang, Hongling; Xu, Jiqian; Yang, Xiaobo; Zou, Xiaojing; Shu, Huaqing; Liu, Zhengdong; Shang, You (Frontiers in Medicine, 2021)
Extracorporeal membrane oxygenation (ECMO), a life-saving technique for patients with severe respiratory and cardiac diseases, is being increasingly utilized worldwide, particularly during the coronavirus disease 2019(COVID-19) pandemic, and there has been a sharp increase in the implementation of ECMO. However, due to the presence of various complications, the survival rate of patients undergoing ECMO remains low. Among the complications, the neurologic morbidity significantly associated with venoarterial and venovenous ECMO has received increasing attention. Generally, failure to recognize neurologic injury in time is reportedly associated with poor outcomes in patients on ECMO. Currently, multimodal monitoring is increasingly utilized in patients with devastating neurologic injuries and has been advocated as an important approach for early diagnosis. Here, we highlight the prevalence and outcomes, risk factors, current monitoring technologies, prevention, and treatment of neurologic complications in adult patients on ECMO. We believe that an improved understanding of neurologic complications presumably offers promising therapeutic solutions to prevent and treat neurologic morbidity.